2022
DOI: 10.3389/fimmu.2022.932722
|View full text |Cite
|
Sign up to set email alerts
|

Gut mucosal immune responses and protective efficacy of oral yeast Cyprinid herpesvirus 2 (CyHV-2) vaccine in Carassius auratus gibelio

Abstract: Cyprinid herpesvirus 2 (CyHV-2) causes herpesviral hematopoietic necrosis (HVHN) disease outbreaks in farmed Cyprinid fish, which leads to serious economic losses worldwide. Although oral vaccination is considered the most suitable strategy for preventing infectious diseases in farmed fish, so far there is no commercial oral vaccine available for controlling HVNN in gibel carp (C. auratus gibelio). In the present study, we developed for the first time an oral vaccine against CyHV-2 by using yeast cell surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…In rainbow trout vaccinated with an oral vaccine against IHNV, IgT and IgM mRNA level was found to be increased in systemic and mucosal tissues, while IgT expression levels in the hindgut were higher than those in systemic tissues [ 13 ]. A similar phenomenon has also been found in crucian carp vaccinated with an oral yeast vaccine [ 26 ]. Here, IgM and IgT expression levels were promoted in the kidney, spleen, and hindgut post vaccination.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In rainbow trout vaccinated with an oral vaccine against IHNV, IgT and IgM mRNA level was found to be increased in systemic and mucosal tissues, while IgT expression levels in the hindgut were higher than those in systemic tissues [ 13 ]. A similar phenomenon has also been found in crucian carp vaccinated with an oral yeast vaccine [ 26 ]. Here, IgM and IgT expression levels were promoted in the kidney, spleen, and hindgut post vaccination.…”
Section: Discussionsupporting
confidence: 77%
“…It was reported that oral delivery of recombinant S. cerevisiae cells could be engulfed by the intestinal epithelial cells of gut in crucian carp, and heterologous protein-specific antibodies could be detected in the serum of vaccinated fish [ 25 ]. This immune response could be rapidly upregulated after booster vaccination [ 26 ]. Results from the present study showed that ORF132 specific antibody in serum was induced after oral administration, and antibody levels in the EBY100/pYD1-ORF132 immunized group were significantly higher than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies hypothesized that the immune responses induced by mucosal (gut) and parenteral immunization are asymmetrical (73). In a previous study, when antigens were delivered via the gut, mucosal and systemic immune responses were elicited, as demonstrated by an increase in the amounts of circulating IgM (74). In contrast, delivering the dinitrophenol (a model antigen) by intraperitoneal injection resulted in strong systemic responses, whereas mucosal responses were virtually absent (75).…”
Section: Discussionmentioning
confidence: 97%
“…Subunit vaccines eliminate irrelevant or harmful pathogen components that induce protective immunity while retaining only the effective immunogenic components, resulting in significantly improved and stable immune effects, increased reliability, and fewer adverse reactions in the body. However, they frequently need optional adjuvants and are incapable of producing mucosal and cellular protection ( 36 ). But the plant-produced subunit vaccines are easier to manufacture, transport and store, and the immunization route is simpler and safer.…”
Section: Classification and Preparation Technology Of Aquatic Vaccinesmentioning
confidence: 99%